Peran Lembaga Studi Islam Al-Awfiya dalam Pembinaan Keagamaan Remaja Jakarta - Ahmad Irfan Irfan; Nurbaiti Bahrudin (Neolectura, 2022)
Teenagers who are the next generation need to get special attention in terms of religious coaching, empowerment and organizational introduction. The reality in society shows that the current religious conditions of Jakarta teenagers are very tough challenges so that special attention is needed to the school family environment and the community. This research uses a Qualitative research approach with an analytical descriptive method with the aim of knowing the process of religious development of Jakarta adolescents at the Al-Awfiya Islamic Studies Institute, to find out the supporting and inhibiting factors for Jakarta adolescent religious development at the Al-Awfiya Islamic Studies Institute, and to determine the impact of religious coaching on the religious behavior of Jakarta adolescents at LSI Al-Awfiya. The primary data of this research was obtained directly from the administrators and members of the Al-Awfiya Institute of Islamic Studies which was carried out through interviews, observations while secondary data was obtained through literature in the form of books, scientific papers and online media. The research site took place in the secretariat and study panel of the Al-Awfiya Institute of Islamic Studies. Data collection techniques use interviews, observations, documentation. Meanwhile, data analysis techniques go through the stages of data reduction, data presentation and conclusion making. The results of this study show that the jakarta adolescent religious development process at the Al-Awfiya Islamic Studies Institute combines traditional and modern curriculum approaches, supporting factors for Jakarta adolescent religious development at the Al-Awfiya Islamic Studies Institute are the infrastructure owned by LSI Al-Awfiya, the attention of local residents and government officials, a network of cooperation that is well established between LSI Al-Awfiya and Educational Institutions and various communities in the community. while the inhibiting factors are the limitations of educators, sources of financing, and the limitations of experts who master technology.